The importance of organic amendments in soil conservation and agricultural production - Murillo Montoya, Sergio Adrián
Organic amendments are used to improve the soil physical, chemical and microbiologicalconditions, allowing to increase the availability ofe macro and micronutrients necessary for plants toimprove their production. Among the main organic amendments are green manures, sewage sludge,manure and vermicompost, which combined with efficient microorganisms, have the potential to improvewater availability for plants, reduce greenhouse gas emissions, and recover degraded soils, reduce erosion,sequester heavy metals and carbon, and solubilize macro and micronutrients necessary for plants. As aconsequence of the above, this review explored the different types of organic amendments that are usedworldwide, evaluated the impact of the addition of efficient microorganisms in organic amendments anddetermined the impact of organic amendments on agricultural production. It was found that, worldwide,amendments are used as cheaper and more affordable alternatives than synthetic fertilizers.